2021
DOI: 10.3390/microorganisms9122510
|View full text |Cite
|
Sign up to set email alerts
|

Single- and Dual-Species Biofilm Formation by Shiga Toxin-Producing Escherichia coli and Salmonella, and Their Susceptibility to an Engineered Peptide WK2

Abstract: Shiga toxin-producing Escherichia coli (STEC) and Salmonella enterica are important foodborne pathogens capable of forming both single- and multi-species biofilms. In this study, the mono- and dual-species biofilms were formed by STEC O113:H21 and Salmonella enterica serovar Choleraesuis 10708 on stainless steel in the presence of beef juice over 5 d at 22 °C. The dual-species biofilm mass was substantially (p < 0.05) greater than that produced by STEC O113:H21 or S. Choleraesuis 10708 alone. However, numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Day 10 produced significantly ( p < 0.05) higher biomass than day 6 surface‐attached cells and were categorized as weak biofilms. Several studies have reported a direct relationship between incubation time and biomass production (Ma et al, 2021; Prasad & Roopesh, 2023; Singla et al, 2014; Visvalingam, Zhang, et al, 2019; Yang et al, 2018). An increase in the biomass production of the mixed‐species consortia has also been positively correlated with disinfection resistance (Burmølle et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Day 10 produced significantly ( p < 0.05) higher biomass than day 6 surface‐attached cells and were categorized as weak biofilms. Several studies have reported a direct relationship between incubation time and biomass production (Ma et al, 2021; Prasad & Roopesh, 2023; Singla et al, 2014; Visvalingam, Zhang, et al, 2019; Yang et al, 2018). An increase in the biomass production of the mixed‐species consortia has also been positively correlated with disinfection resistance (Burmølle et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella can survive in low-moisture foods such as powdered milk, chocolate, peanut butter, infant foods, cereal, and bakery products over extended periods of time [42]. Salmonella is known to form biofilms on glass slides [43] and stainless steel [44,45]. The ability to form biofilms enhances the ability of Salmonella to survive in food-processing plants.…”
Section: Factors Impacting Cross-contamination Of Pathogens Occurrenc...mentioning
confidence: 99%